Patent Mapping of Coffee Residues Utilization in Brazil, Latin America and the World - Franchi, Rosângela Aparecida da Silva (2022)
Brazil is the largest coffee producer in the world and produces a huge amount of waste that impacts the environment but that can be used sustainably. On the other hand, the USA and Germany are the biggest importers of the drink and also generate significant residues. The study consists of researching and pointing out, through technological information extracted from patent documents in the database of Brazil's National Institute of Industrial Property (INPI) and the search tools Latipat-Espacenet and Derwent Innovations Index, some possibilities for using coffee residues. It is an exploratory research in terms of objectives, with a qualitative and quantitative approach, using bibliographic and documentary research procedures. The study concludes that it is possible to transfer the data contained in patent documents, especially to identify technological innovations and point out the underutilization that Brazil gives to coffee residues with the possibility of generating new products with high added value.